Translocation process of structured polypeptides across nanopores. Issue 3 (2010) - Cecconi, Fabio; Marconi, Umberto Marini Bettolo; Vulpiani, Angelo
Abstract : The progress of molecular manipulation technology has made it possible to conduct controlled experiments on translocation of polynucleotide and polypeptide chains across alpha-Hemolysin channels and solid-state nanopores. To study the translocation process we combined Molecular Dynamics at coarse-grained level and appropriate drift-diffusion Smoluchowski equations as an integrated statistical physics approach. In particular, we performed simulations of the passage across a cylindrical nanopore of Ubiquitin described by a coarse-grained native-centric model to investigate the influence of protein structural properties on translocation mechanism. The kinetic characterization of the process is achieved by studying the statistics of blockage times, the mobility and translocation probability as a function of the pulling force F acting in the pore. We find that the transport dynamics displays a threshold Fc depending on a free-energy barrier that Ubiquitin overcomes to translocate. Our simulations show this barrier to be the result from competition of the unfolding energy and the entropy associated to the confinement effects of the pore.